Pendampingan Pembuatan Basreng Dalam Meningkatkan Pendapatan Masyarakat di Lembang Pitung Penanian - Jens B Marewa; Elim Febrianty Bintan; Sumardianto Ishak Masiku (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
Community Service Activities are carried out to strengthen community capacity and empowerment. This service activity aims to enable PKK Lembang Pitung Penanian women to produce a variety of Basreng products. This service uses a mentoring method, consisting of four mentoring activities, namely assistance in making Basreng products, product packaging, improving product quality, using tools and expanding marketing. The output of this assistance activity is the existence of varied products, applied product packaging designs, the use of quality raw materials, the use of sales displays to make them more attractive and mapping market expansion through opening new areas. The result of this activity is business development through measurable, controlled and coordinated market expansion